Stress drop effects in time dependent behavior of quartz sand. (1st June 2016) - Lade, Poul V.; Karimpour, Hamid
Abstract: Time effects in granular materials relate to crushing of grains, which is a time dependent process. Depending on the proximity of the load applied to a grain relative to the instantaneous failure load of the grain, the time increases as the load is decreased below the failure load. A study of grain crushing associated with stress drop-creep and stress drop-stress relaxation experiments on dense Virginia Beach sand consisting mainly of quartz grains is presented. In these experiments the triaxial specimens are isotropically consolidated to 8000 kPa, sheared at a constant rate up to a given deviator stress followed by either creep or stress relaxation over a given time period. After dismantling the triaxial specimens, the grain size distributions are determined and their changes, as expressed through Hardin's relative breakage factor, are related to the amount of energy input. Results of the stress drop-creep tests and the stress drop-stress relaxation tests show that creep deformations and the amount of stress relaxation are considerably reduced with increasing amounts of stress drop. Depending on the amount of stress drop, a delay is detected before creep deformation or stress relaxation is initiated. Multiple stress drop-creep experiments are also performed. Structuration effects, which describe changes in yield surface location during creep or stress relaxation and are due to change in grain configuration and interlocking with time, are not observed in the specimens of Virginia Beach sand.